Development of a Joint Commission Disease-Specific Care Certification Program for Parkinson Disease in an Acute Care Hospital. Issue 6 (December 2019) - Azmi, Hooman; Cocoziello, Lisa; Harvey, Renee; McGee, Margaret; Desai, Nilesh; Thomas, Jewell; Jacob, Blessy; Rocco, Anthony; Keating, Karen; Thomas, Florian P.
ABSTRACT: BACKGROUND: Patients with Parkinson disease (PD) admitted to the hospital for any reason are at a higher risk of hospital-related complications. Frequent causes include delays in administering PD medications or use of contraindicated medications. The Joint Commission Disease-Specific Care (DSC) program has been used to establish a systematic approach to the care of specific inpatient populations. Once obtained, this certification demonstrates a commitment to patient care and safety, which is transparent to the public and can improve quality of care. METHODS: We formalized our efforts to improve the care of hospitalized patients with PD by pursuing Joint Commission DSC. An interprofessional team was assembled to include nurses, therapists, physicians, pharmacists, performance improvement specialists, and data analysts. The team identified quality metrics based on clinical guidelines. In addition, a large educational campaign was undertaken. Application to the Joint Commission for DSC resulted in a successful June 15, 2018 site visit. To our knowledge, this is the first DSC program in PD in an acute care hospital. CONCLUSION: Using the established platform of DSC certification from the Joint Commission, we developed a program based on relevant metrics that aims to address medication management of patients with PD admitted to the hospital. Our hope is to improve the care of this vulnerable patient population. Abstract : Supplemental digital content is available in the text.